Cobalt(III)-Catalyzed 1,4-Addition of C(sp3)–H Bonds to Maleimides - Chen, Xiang-Xiang; Ren, Jiang-Tao; Xu, Jing-Lei; Xie, Hu; Sun, Wei; Li, Ya-Min; Sun, Meng (Synlett, 2018)
Quinolines and succinimides play a crucial role in many pharmaceutical and natural products. Although sp2 C–H bond addition reactions have been extensively investigated, Co(III)-catalyzed sp3 C–H bond 1,4-addition reactions are relatively unexplored. In this manuscript, an efficient and atom-economic protocol for alkylation reactions of 8-methylquinolines with maleimides is presented. The reaction exhibits exceptional reactivity, satisfactory yields, excellent chemo- and regioselectivity, and tolerates a variety of functional groups.
Keywords: cobalt; 1,4-addition reactions; alkylation; C–H functionalization; 8-methylquinolines